2020
DOI: 10.1016/j.medin.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Infección grave por coronavirus SARS-CoV-2: experiencia en un hospital de tercer nivel con pacientes afectados por COVID-19 durante la pandemia 2020

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
6
18
1
1
Order By: Relevance
“…ICU admission represents 1.4% of all cases diagnosed and 5.1% of COVID-19-related hospital admissions. The percentage of patients admitted to the ICU is far from the 11.3% reported by Rodríguez et al [ 19 ], although close to the 7% published by Yang et al [ 20 ].…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…ICU admission represents 1.4% of all cases diagnosed and 5.1% of COVID-19-related hospital admissions. The percentage of patients admitted to the ICU is far from the 11.3% reported by Rodríguez et al [ 19 ], although close to the 7% published by Yang et al [ 20 ].…”
Section: Discussionmentioning
confidence: 47%
“…In over half our patients (55.6%) NIV was tested and failed; MV was required in 100% of patients. Other authors have reported high levels of failure of NIV: 85.2% in the Tarragona study [ 19 ]. In the Lombardy and Washington series barely 11% and 19% respectively only received NIV, while the number of patients receiving MV after having received NIV is not specified [ 25 ] and Hua et al report 32.5% of patients treated with NIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PaO2/FiO2 ratio on the day of ICU admission was 132(IQR 96-163) and 1,131 (55•9%) patients meet criteria of severe and 198(9•8%) of mild acute distress respiratory syndrome (ADRS) pro le at ICU admission, 1,174 (58.0%) patients required invasive mechanical ventilation (MV), 906 (44.8%) developed shock and 580 (28.7%) meet criteria of acute kidney injury (AKI). The overall ICU length of stay (LOS) was 14 (8-26) days and similar for survivors (14[8-27]) days and non-survivors (14 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]) days (p=0•10).…”
Section: Resultsmentioning
confidence: 99%
“…c SOFA score corresponds to the severity of organ dysfunction, re ecting six organ systems each with a score range of 0 to 4 points (cardiovascular, hepatic, hematologic, respiratory, neurological, renal), with a total score range of 0 to 24, White blood cell, median (IQR), x10 9 8.4(6.1) 9.7 (6.6-13.6) .001…”
Section: Resultsmentioning
confidence: 99%